A Walk in Victoria's Secret : Poems - Daniels, Kate, 1953- (Book collections on Project MUSE., 2010)
With A Walk in Victoria's Secret, Kate Daniels crafts a bold, brassy, yet delicate vision of a woman's growth. Imbued with a unique poetic voice that is utterly feminist, these poems possess a fiery intensity before those abuses no woman can ever quite recover from, but also reveal the loving, forgiving temperament of the mother no woman can do without. From the title poem's unapologetic celebration of the breast to a belated apology to the young girl who integrated her elementary school, to the awkward juxtaposition of elderly and young women in a gynecologist's office on September 11, 2001.